'A True Magic Chamber': The Public Face of the Modernist Bookshop. Issue 3 (November 2016) - Thacker, Andrew
Abstract : This article explores the role of bookshops in the construction of a public for modernism and analyses a number of bookshops committed to promoting modernist culture, such as those run by Sylvia Beach (Shakespeare and Company), Adrienne Monnier (La Maison des Amis des Livres), and Frances Steloff (Gotham Book Mart). It also considers how the bookshop is a fulcrum between commerce and culture, a key issue for contemporary modernist studies, and discusses aspects of bookshop culture that seem to operate 'beyond' the market. One example is that of We Moderns, a catalogue issued by the Gotham Book Mart in 1940 and which represents a fascinating example of the print culture of the modernist bookshop. Drawing upon the work of Mark Morrisson and Lawrence Rainey, the article also evaluates the position of the bookshop within debates around modernism and the public sphere.